Facing the climate challenge [videorecording (DVD)]. - Murdock, David; O'Brien, Miles; O'Brien, Miles; Boffey, Mercer, 1982-; Galindo, Eileen (PBS Distribution, 2023)
Explore ways that scientists are facing the climate challenge, including reprecussions of permafrost thaw, ameliorating extreme weather, and attempts to achieve net-zero carbon emissions.